2019
DOI: 10.18203/2320-6012.ijrms20191655
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intracuff dexamethasone in reducing the incidence of post-operative sore throat: an original article

Abstract: Background: Postoperative sore throat is the most common and most distressing complaint of patients after general anaesthesia with cuffed endotracheal tube. By this study our aim was to assess the efficacy of intracuff dexamethasone in reducing the incidence of this distressing postoperative symptom. Methods: Patients were divided into two groups D and N depending on cuff filling with dexamethasone and normal saline respectively. The cuff was prefilled with dexamethasone or normal saline one hour prior to intu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Another study by Sugathan et al . 4 showed that intracuff dexamethasone 8 mg reduced the incidence of POST and POC as compared to intracuff normal saline but not postoperative hoarseness of voice.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another study by Sugathan et al . 4 showed that intracuff dexamethasone 8 mg reduced the incidence of POST and POC as compared to intracuff normal saline but not postoperative hoarseness of voice.…”
Section: Discussionmentioning
confidence: 94%
“…Of late, studies have shown that use of intracuff dexamethasone can be an be effective method in reducing postoperative pharyngo-laryngeal complications. [ 2 3 4 ] The primary objective of the present study was to compare the effect of intracuff dexamethasone on the incidence and severity of POST. The secondary objectives included comparison of the effect on postoperative hoarseness of voice (POHV) and cough (POC).…”
Section: Introductionmentioning
confidence: 99%